Ethnicity-related adult education cultural diversity programs: A typology - Larry G. Martin (Adult Education Research Conference, 1994)
Organizations that experience ethnicity-related problems often identify cultural diversity training as a solution. However, there are multiple approaches and perspectives to such programs and programmatic outcomes will vary considerably with the approach selected. A typology is presented which identifies five types of programs.